Enhanced Recovery after Abdominoplasty Using Perisurgical Nutritional Supplementation. Issue 12 (December 2020) - Harris, Leonard; Darby, Peter
Abstract : Background: Nutritional supplements are common in other surgical specialties but not widely used in the plastic surgery setting. This study compares the surgical outcomes of patients using our standard ERAS protocol involving arnica and bromelain with an updated ERAS protocol using perisurgical nutritional supplementation using a staged administration of nutraceuticals. Methods: In total, 300 female abdominoplasty patients were randomly provided with perioperative supplementation consisting of arnica and bromelain, or a 3-stage nutraceutical regimen containing arginine, citrulline, glutamine, bromelain, and vitamin C. Narcotic use in recovery and post-operative drainage were measured, and both groups completed a self-assessment of bruising coloration, days to independent activity, perceived pain, and documented the quantity of narcotic and non-prescription pain killers they took over a 14-day recovery period. Results: There were 130 patients in the nutraceutical group and 80 in the arnica and bromelain group; patients were excluded due to non-compliance or due to incomplete data. Patients taking the nutraceutical regimen reported a shorter duration of pain and had a 41% reduction in narcotic use in recovery and experienced 48% less post-operative drainage. Home use of narcotic pain killers decreased by 25%. There also was a trend toward decreased and earlier clearing/maturation of bruising as well as return to daily activates without assistance. Patients also reported an increase in satisfaction with their surgical experience. Conclusions: This study demonstrated that perioperative supplementation with nitric oxide precursors, antioxidants, and proteolytic enzymes in a staged fashion can positively affect post-operative outcomes and is an adjunct to enhanced surgical recovery protocols.